The mastery of religious based secondary school student on the education of arabic rhetoric - Muhammad, Azhar; Abdullah, Abdul Hafiz; Basiron, Bushrah; Jasmi, Kamarul Azmi; Mohd. Noor, Sulaiman Shakib (Universiti Teknologi Malaysia, 2005)
Religious based secondary school. It is done in order to determine the perception and knowledge of student on the al-Balaghah knowledge, identify the problems faced by student in Arabic literature knowledge education and to identify the effectiveness of teaching and learning of Arabic literature knowledge education among the student and the application of this knowledge in their language style. 320 form five students from religious based secondary schools in Johor was chosen as sample for this study. This research uses questionnaires in order to obtain research data and the data obtained is processed using Likert scale. Result of this study shows that the students have deep perception and interest on the al-Balaghah knowledge and the result also shows that the teaching of al-Balaghah knowledge in chosen schools is effective in increasing the student mastery on the al-Balaghah knowledge. Unfortunately, there are few problem facing these students had been identified which could prevent them from mastering this knowledge. To ensure that the students can master the Balaghah knowledge as much as they can, researchers suggested a few steps that can be taking account by Ministry of Education, school committee and the teachers.